Conjugate heat and mass transfer in square porous cavity - Azeem, -; Badruddin, Irfan Anjum; Idris, Mohd Yamani Idna; Nik-Ghazali, Nik Nazri; Salman Ahmed, N.J.; Al-Rashed, A.A.A.A. (National Institute of Science Communication and Information Resources (NISCAIR), 2016)
The present article deals with the issue of heat and mass transfer in a square porous cavity having a small solid wall or block inserted at various places at bottom surface. The main objective is to investigate the effect of size of solid wall and its location inside the porous cavity on double diffusive convention. The heat and mass transfer behavior are governed by momentum, energy and concentration equations which are converted into a set of finite element equation with the help of Galerkin method. The left surface of cavity is maintained at higher temperature and concentration, Th and Ch as compared to that of right surface at Tc and Cc. The results are presented in terms of thermal, concentration and fluid flow profiles across the porous cavity.